The Growing Importance of Staple Foods and Condiments Used as Ingredients in the Food Industry and Implications for Large-Scale Food Fortification Programs in Southeast Asia. Issue 2 (June 2013) - Spohrer, Rebecca; Larson, Melanie; Maurin, Clémence; Laillou, Arnaud; Capanzana, Mario; Garrett, Greg S.
Background: Food fortification is a viable strategy to improve the nutritional status of populations. In South-east Asia, recent growth and consolidation of the food industry provides an opportunity to explore whether certain widely consumed processed foods could contribute to micronutrient status if they are made with adequately fortified staples and condiments. Objective: To estimate the potential contribution certain processed foods can make to micronutrient intake in Southeast Asia if they are made with fortified staples and condiments; e.g., via the inclusion of iodized salt in various processed foods in the Philippines, fortified wheat flour in instant noodles in Indonesia, and fortified vegetable oil in biscuits in Vietnam. Methods: For Indonesia, the Philippines, and Vietnam, a review of consumption trends, relevant policies, and industry practices was conducted using publicly available sources, food industry market data and research reports, and oral communication. These informed the estimates of the proportion of the Recommended Nutrient Intake (RNI) that could be delivered via select processed foods. Results: In the Philippines, Indonesia, and Vietnam, the processed food industry is not always required to use fortified staples and condiments. In the Philippines, dried salted fish with iodized salt would provide 64% to 85% of the iodine RNI for women of reproductive age and 107% to 141% of the iodine RNI for children 1 to 6 years of age. In Indonesia, a 75-g pack of instant noodles (a highly consumed product) with fortified wheat flour would provide 45% to 51% of the iron RNI for children 4 to 6 years of age and 10% to 11% of the iron RNI for women of reproductive age. In Vietnam, biscuits containing vegetable oil are increasingly popular. One 35-g biscuit serving with fortified vegetable oil would provide 13% to 18% of the vitamin A RNI for children 4 to 6 years of age and 12% to 17% of the vitamin A RNI for women of reproductive age. Conclusions: Ensuring that fortified staples and condiments such as flour, salt, and vegetable oil are used in widely consumed processed foods would ensure that these foods contribute to improvement in micronutrient intake among populations in Southeast Asia, particularly as the consumption of these foods is increasing. Policymakers and nutrition program managers should consider the contribution to nutritional intake that fortified staples and condiments can provide through processed foods, in addition to being used for cooking in the home, and ensure that the food industry is required to use these fortified staples and condiments rather than nonfortified foods.